Analisis Persepsi Guru Sekolah Dasar terhadap Projek Penguatan Profil Pelajar Pancasila di Kabupaten Sumedang - Tatang Suryadi; Dinn Wahyudin (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The independent curriculum is a term used for changes to the curriculum currently in use. The difference in the independent curriculum with the previous curriculum is the recognition of cocurricular activities that were previously given less attention and carried out spontaneously without careful planning. The purpose of this study was to determine the perceptions of elementary school teachers towards the Pancasila Student Profile Strengthening Project (P5) in implementing the independent curriculum. This research uses a quantitative approach with a descriptive type. The method used is the survey method and the respondents in this study were elementary school teachers in Sumedang Regency using a simple random sampling technique. Data collection techniques using questionnaires, interviews and documentation. The questionnaire was distributed to elementary school teachers in Sumedang Regency via Whatsapp using google form media. The number of teachers who became respondents was 76 teachers. In this study, the data analysis method adopted the Miles and Huberman model, which consists of the steps of data reduction, data presentation, and conclusion drawing. The results showed that teachers' understanding of P5 in implementing the independent curriculum was in the sufficient category. So an effort is needed to improve teachers' understanding of P5, one of which is by utilizing the Merdeka Mengajar Platform as a means of independent training for teachers. It is hoped that the use of Merdeka Mengajar Platform can improve teachers' understanding of P5 in independent curriculum.